2012
DOI: 10.1093/cvr/cvs001
|View full text |Cite
|
Sign up to set email alerts
|

GATA4 expression is primarily regulated via a miR-26b-dependent post-transcriptional mechanism during cardiac hypertrophy

Abstract: Down-regulation of miR-26b in the heart is required for the up-regulation of GATA4 and the induction of pressure-induced cardiac hypertrophy. The results also underscore the functional relevance of miRNAs in regulating gene expression during cardiac hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 24 publications
4
68
0
Order By: Relevance
“…Emerging evidence has suggested that a number of miRNAs are important in the regulation of adipocyte differentiation, including the miR-143 (9) and miR-1792 clusters (10). miR-26b is an intronic miRNA encoded in the carboxy-terminal domain, RNA polymerase II, polypeptide A, small phosphatase 1 (CTDSP1) gene that is important in a variety of different diseases, including lung carcinoma, breast cancer and cardiac hypertrophy (11)(12)(13). However, there have been few studies investigating the role of miR-26b in obesity and insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has suggested that a number of miRNAs are important in the regulation of adipocyte differentiation, including the miR-143 (9) and miR-1792 clusters (10). miR-26b is an intronic miRNA encoded in the carboxy-terminal domain, RNA polymerase II, polypeptide A, small phosphatase 1 (CTDSP1) gene that is important in a variety of different diseases, including lung carcinoma, breast cancer and cardiac hypertrophy (11)(12)(13). However, there have been few studies investigating the role of miR-26b in obesity and insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…miR-26b seems to be involved in cardiac hypertrophy by regulating GATA4, a transcription factor that increases alpha-skeletal actin and atrial natriuretic factor, 2 factors relevant for cardiac hypertrophy. 29,30 Recently, miR-26b was reported to be implicated in nitric oxide and atrial natriuretic peptide signaling in vascular smooth muscle cells. 40 In conclusion, the present study provides the first evidence of 3′-UTR-directed regulation of HSD11B2 mRNA by miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Primary cardiomyocyte culture, transfection, and immunofluorescence: Primary cardiomyocytes were isolated from neonatal C57Bl/6 mice 7) and cultivated in 6 well plates with Dulbecco's modified Eagle's medium (DMEM)/F12 supplemented with 110 U/mL penicillin, 100 μg/mL streptomycin, and 10% fetal bovine serum (Gibco) in humidified air (5% CO 2 ) at 37°C. For transfection or chemical treatments, cells were seeded into 6-well culture plates (5-10 × 10 4 cells/cm 2 ) and serumstarved for 18 hours, and either infected with lentivirus at a multiplicity of infection (MOI) of 100 or with cardiotrophin-1 (CT-1) (1nM), isoprenaline (ISO,10 μM) and leukemia inhibitory factor (LIF) (1000 U/mL) for 48-72 hours.…”
Section: Methodsmentioning
confidence: 99%
“…4,5) Increasing evidence has demonstrated dysregulated expression patterns of specific miRNAs could alter the cellular response of cardiomyocytes, leading to the pathology of cardiac concentric hypertrophy and heart failure. 2,[6][7][8] For example, miR-133 was down-modulated in hypertrophic human heart and played a role in HF via target genes RhoA, Cdc42 and Nelf-A/ WHSC2; 9) miR-195 transgenic mice showed pathological cardiac growth and heart failure; 3) and the transcription of miR23a was activated by nuclear factor of activated T cells (NFAT) whose hypertrophic effect was ascribed to miR-23a. 10) Previously we found some dysregulated miRNAs in failing human hearts caused by dilated cardiomyopathy, in which micrRNA-340-5p (miR-340) represented the most significant difference (2.6 fold upregulation).…”
mentioning
confidence: 99%